The growth of Finnish software companies in 2008-2011 : empirical investigation of financial ratios as the determinants of growth - Kaasalainen, Mikko (2014)
The purpose of this study is to examine the relation of growth and the financial ratios of a company. The theoretical portion of the study focuses on the concept of growth in entrepreneurship theory. The empirical portion consists of examination of the financial ratios of 162 Finnish software companies in 2008-2011 by means of quantitative analysis methods. Statistical analysis methods, including analysis of variance, correlation and regression analysis, are used in the analysis. The objective of the study is to reveal how growth affects the financial ratios of a company and which ratios can be used to predict growth. The effects of companies’ age, geographical location and industrial classification on their financial ratios are also examined.